2017
DOI: 10.2105/ajph.2017.303695
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mental, and Financial Impacts From Drought in Two California Counties, 2015

Abstract: Drought-impacted households might perceive physical and mental health effects and might experience financial or property impacts related to the drought. Public Health Implications. Local jurisdictions should consider implementing drought assistance programs, including behavioral health, and consider rapid assessments to inform public health action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Similarly, mosquito-borne diseases may cause long-term cognitive, functional, and movement disorders (Hughes, Wilson, and Sejvar 2007). Many case studies document the chronic psychologic dysfunction of survivors of catastrophic extreme events (e.g., hurricanes, floods, drought) ( Barreau et al 2017;Bei et al 2013;La Greca et al 2010). However, there is less systematic evidence of the mental health impacts of less severe but more common extreme events.…”
Section: Research Gapsmentioning
confidence: 99%
“…Similarly, mosquito-borne diseases may cause long-term cognitive, functional, and movement disorders (Hughes, Wilson, and Sejvar 2007). Many case studies document the chronic psychologic dysfunction of survivors of catastrophic extreme events (e.g., hurricanes, floods, drought) ( Barreau et al 2017;Bei et al 2013;La Greca et al 2010). However, there is less systematic evidence of the mental health impacts of less severe but more common extreme events.…”
Section: Research Gapsmentioning
confidence: 99%
“…Respondents of a Community Assessments for Public Health Emergency Response (CASPER) health impact assessment conducted in Calfornia USA reported worsening of respiratory conditions including asthma and allergies upon perceived increased amounts of dust during the drought period (Barreau et al 2017). An inverse association between Palmer Hydrological Drought Index (PHDI), an index of hydrological drought, and the prevalence of hayfever across the states in the United States was also reported, such that drier states had more hayfever.…”
Section: Necrotizing Fasciitismentioning
confidence: 99%
“…Respondents of a health impact assessment conducted in Calfornia USA reported that the drought had a negative impact on their household's peace of mind or that a drought-related experience in the past 30 days lead to acute mental stress (Barreau et al 2017). Some respondents also reported worsening of preexisting mental conditions of someone in their household since the drought began (Barreau et al 2017).…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…The water level of the Salton Sea, located centrally within Imperial County (Figure 1), has been diminishing as a result of evaporation and decreased precipitation and river flow. California's most severe drought took place between the years 2012 and 2017 (Barreau et al, 2017; Griffin & Anchukaitis, 2014), including four of those years under a government‐declared state of emergency.…”
Section: Introductionmentioning
confidence: 99%